Enforcement authorities as subjects of the inclusive education in Ukraine - Миськів, Леся Ігорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In the article the author characterizes authorities of the central bodies of the executive power of Ukrainein the sphere of realization of the inclusive education. Authorities of the Cabinet of Ministers of Ukraine, theMinistry of education and science of Ukraine, the Ministry of health protection of Ukraine, the Ministry ofsocial policy of Ukraine and also local state administrations are disclosed.